Construction processes of roof structures: a systematic review - Thaisa Lana Pilz; Mayara Scheuer; Marcell Mariano Corrêa Maceno; Thalyta Genaro; Nicolle Christine Sotsek (The Journal of Engineering and Exact Sciences)
Despite the fact that the construction industry in Brazil is traditionally recognized for the use of craft construction techniques, in the last few years, there has been a growth in the search for new materials, processes, and technologies for this segment.  This is mainly due to the great environmental impact that this sector causes. Based on this context, this article aimed to map the constructive processes of existing roofs in the literature, to raise its advantages, disadvantages and previous cases. To achieve this aim, the systematic review method based on three phases –  research questions, selection of documents and classification of selected documents, and the 5W2H quality tool were used. Thus, this research could contribute to the literature on this topic, as well as encourage the idealization of new ideas of roof construction processes.